2023
DOI: 10.1124/dmd.122.000968
|View full text |Cite
|
Sign up to set email alerts
|

Predicting In Vivo Target Occupancy (TO) Profiles via Physiologically Based Pharmacokinetic–TO Modeling of Warfarin Pharmacokinetics in Blood: Importance of Low Dose Data and Prediction of Stereoselective Target Interactions

Abstract: ordinary differential equation; K p , the tissue-to-blood partitioning coefficients; K d , the equilibrium dissociation constant; k a , the absorption rate constant; k on , the association rate constant; k off , the dissociation rate constant; CYP, cytochrome P450; PS, the permeability surface product; V d , the volume of distribution; CL, clearance; CL int,all , the overall intrinsic clearance; X TotalR , the total amount of the receptor; V max , the maximum rate in the Michaelis-Menten equation; CGNM, the Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…PBPK modeling of warfarin has previously been applied to investigate specific scenarios, such as studying bioequivalence, 57 determining the role of OAT2, 35 predicting in vivo target occupancy, 38 and DDI. 59,66,69 Two studies of PBPK/PD modeling are applied to dose management when warfarin and sorafenib or nirmatrelvir/ ritonavir are administered in combination.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PBPK modeling of warfarin has previously been applied to investigate specific scenarios, such as studying bioequivalence, 57 determining the role of OAT2, 35 predicting in vivo target occupancy, 38 and DDI. 59,66,69 Two studies of PBPK/PD modeling are applied to dose management when warfarin and sorafenib or nirmatrelvir/ ritonavir are administered in combination.…”
Section: Discussionmentioning
confidence: 99%
“…As early as 1994, Professor Levy proposed the TMDD for warfarin and subsequently simulated blood concentration profiles in rats and humans using the PBPK model 36,58 . Two recently published PBPK models for warfarin consider the effect of TMDD on warfarin, and both improve the model compared to models that do not incorporate TMDD 38,59 . In this study, the model was greatly improved by adding the TMDD process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this way, the user can discuss and draw a conclusion about the simulation study while considering multiple possible simulation results that originate from the fact that some parameters are not identifiable. For example, recently, Lee et al 14 have shown that the despite that not all model parameters can…”
Section: Cluster Gauss-newton Methodsmentioning
confidence: 99%